Improving Environmental Vocabulary Mastery of Grade 11 Students through Multi-game Intervention - Emiliana Uge; Priscilla Maria Assis Hornay (JET (Journal of English Teaching), 2026)
Environmental vocabulary is a fundamental component of EFL learning, enabling students to understand texts and communicate effectively about sustainability issues. However, Indonesian learners often struggle with environmental terminology due to limited exposure and traditional teacher-centered instruction. This pre-experimental study investigated the effectiveness of a multi-game intervention—Crossword Puzzles, Vocabulary Bingo, Word Chain, and Kahoot—in improving Grade 11 students’ environmental vocabulary mastery. Using a one-group pretest–posttest design involving 17 grade 11 students, a 20-item environmental vocabulary test measured changes in performance. Results showed a substantial gain: mean scores increased from 9.82 (49.10%) to 17.59 (87.95%), with 70.59% of students achieving the Advanced mastery level after the intervention. A paired sample t-test confirmed a significant difference between pretest and posttest scores (p = .000). The findings align with prior research demonstrating that game-based learning enhances motivation, strengthens vocabulary recall, and supports deeper lexical processing. This study recommends integrating diverse games into vocabulary teaching, especially for thematic domains such as environmental education.